A Novel Oxopyrimidine and Pyrazole Derivatives: Synthesis, Characterization and Biological Activity Study - Ali, Rana Abid; Dhedan, Ruaa M. (Iraqi Journal of Science, 2025)
Novel oxopyrimidine (3,7) and pyrazole (4,8) compounds bearing an azo group were successfully synthesized and characterized using FTIR, 1HNMR, and 13CNMR spectroscopy. The diazonium salt was first synthesized by reacting p-amino acetophenone with nitrous acid. This salt was added to activated aromatic rings (o-nitro phenol, β-naphthol) to produce azo compounds (1,5). Following the reaction of these azo compounds with salicylaldehyde, chalcone derivatives (2,6) were produced. Subsequently, these synthetic compounds were cyclized to create pyrazole derivatives (4,8) and oxopyrimidine (3,7) using urea and 2,4-dinitrophenyl hydrazine. Furthermore, the antibacterial activity of synthesized compounds was elevated against two types of bacteria (Pseudomonas and Staphylococcus aureus. According to the results, compounds 1-[4-(4-Hydroxy-3-nitro-phenylazo)-phenyl]-ethanone (1) and 1-[4-(2-Hydroxy-naphthalen-1-ylazo)-phenyl]-ethanone (5) were effective in treating the selected bacterium, while the other compounds are inactive